Asymmetries in the Acceptability and Felicity of English Negative Dependencies: Where Negative Concord and Negative Polarity (Do Not) Overlap - Blanchette, Frances; Lukyanenko, Cynthia (Frontiers in Psychology, 2019)
Negative Concord (NC) constructions such as the news anchor didn’t warn nobody about the floods (meaning ‘the news anchor warned nobody’), in which two syntactic negations contribute a single semantic one, are stigmatized in English, while their Negative Polarity Item (NPI) variants, such as the news anchor didn’t warn anybody about the floods, are prescriptively correct. Equating acceptability with grammaticality, this pattern has led linguists to treat NC as ungrammatical in “Standard” or standardized English (SE). However, it is possible that SE grammars do generate NC sentences, and their low incidence and acceptability is instead due to social factors. To explore this question, and the relationship between NC and NPI constructions, we compared the acceptability of overtly negative noun phrases (e.g. nobody), NPIs (e.g. anybody), and bare plurals (e.g. people), in negative contexts and in conditionals. Negative items were followed by a consequence which supported their single negative meaning, while conditional items were followed by a consequence compatible with the NPI and the bare plural but not the negative noun phrase. Acceptability ratings of the critical NC sentences were reliably lower than constructions with NPIs and bare plurals, but the consequences for all three of these sentence types were rated highly. This reflects an asymmetry in participants’ acceptance of NC and their readiness to interpret it in context. A follow-up study with only conditionals revealed that speakers can also find NPIs infelicitous in conditional contexts with consequences that are compatible with a negative interpretation of the NPI, and that negative arguments are felicitous in these same contexts. Taken together, the results support the hypothesis that speakers who do not accept NC have grammars that generate both NC and NPI constructions, and further, that these speakers have two underlying structures for any-NPIs in English.